Disease activity and fatigue in juvenile idiopathic arthritis1. Issue 3 (26th February 2013) - Ringold, Sarah; Ward, Teresa M.; Wallace, Carol A.
Abstract: Objective: To examine the association between parent/proxy‐ and child‐reported fatigue and disease activity in children with polyarticular, extended oligoarticular, and persistent oligoarticular juvenile idiopathic arthritis (JIA). Methods: We enrolled a cross‐sectional cohort of 309 children recruited from the Seattle Children's Hospital rheumatology clinic from 2009–2011. Parents and children completed the PedsQL Multidimensional Fatigue Scales. The parent/proxy, child, and/or physician provided additional disease activity data at each clinic visit, including active joint count, pain, and the Childhood Health Assessment Questionnaire (C‐HAQ). Disease activity was dichotomized as active or inactive using the American College of Rheumatology provisional criteria for clinically inactive disease. The Juvenile Arthritis Disease Activity Score (JADAS) was also calculated. Linear regression was used to examine the associations between fatigue and disease activity. Results: Associations among fatigue, clinically inactive disease, and the JADAS were not statistically significant after controlling for pain. In the multivariable models of fatigue, the C‐HAQ and parent/child‐reported disease activity were significantly associated with fatigue; however, only the C‐HAQ remained significantly associated after adjustment for pain. The C‐HAQ and parent/child‐reported disease activity explained 17% and 30% of the variance in fatigue for the parent/proxy‐ and child‐reported multivariable models, respectively. Conclusion: In this cohort, functional ability, as measured by the C‐HAQ, was significantly associated with fatigue. Child‐ and parent/proxy‐reported pain were important confounders of the relationship between fatigue and disease activity. Routinely incorporating pain and fatigue into interventional and observational trials of JIA will enable better delineation of the relationships between these variables.